Investigation of metocean interaction behaviour model with offshore structures near the free surface - Mushtaq, Ahmed Nizamani (2022)

(untitled)
The study of metocean interaction around free surface is critical for determining the safety of offshore buildings. Previously, this assessment was done using experimental and analytical techniques, but due to technological advancements, numerical methods are now the most extensively used for assessing the impact of metocean characteristics such as offshore wave and current on fixed and floating offshore installations. In the numerical tank, the numerical models may quickly generate geometries of physical models with realistic offshore settings. Validation and verification of numerical model is frequently required before performing actual model testing. For model testing and fluid-structure interaction modelling, ANSYS Fluent is used to create a two-dimensional rectangular numerical tank. The continuity and ReynoldsAveraged Naiver-Stokes (RANS) equations are governing equations for numerical modelling. In the wave tank, Stokes waves are created. To examine the behaviour of a metocean interaction model near the free surface with offshore structures, three objectives were specified. The first objective of the study was to generate the ocean environments in the numerical tank. The second objective of the study dealt with Fluid-Structure Interaction at two different Reynolds numbers. The last objective involved Wave Structure Interaction (WSI) near the free surface of a fixed offshore platform deck. The study's first objective is met by building two numerical models having a smooth and curved bottom boundary, respectively. The simulation results of the smooth bottom boundary tank are compared with the theory and the curved bottom boundary tank are compared with the experiment. All the wave equations are Stokes second order waves because they satisfy the Ursell parameter. All of the simulated outcomes' free surface heights closely match the ideal wave altitudes, indicating that the study's initial goal has been met. To achieve the second objective, for two reference values Reynolds number (Re) 3900 and 10000, two turbulence models are utilised. When compared to the experiment, the realisable k epsilon (RKE) turbulence model produced more accurate lift and drag coefficient values. It had a good agreement with the experimental data available, with a discrepancy of less than 10%. To achieve the last objective, the rectangular deck is inserted into the tank after successful model testing to determine the wave-in-deck loads. The results show that when water comes into contact with the deck, the velocity towards the upstream edge becomes negative and changes direction. A constant velocity of 0.3 ms-1 is experienced in the tank which increases near the free surface when water moves near the edges of the deck. Lifting forces generated from wave-in-deck loads of current simulations are compared with the experimental results. An error of less than 3% is observed during the maximum lifting force while an error of 15% is observed during the minimum lifting force during this comparison. It is concluded from the study that CFD results agree well with analytical and experimental results.